Triad Triggers of Clinical Injury: The Effect of Workload and Organizational Culture on Needle Stick Injury through Risk Perception - Ida Ayu Gede Karuni Sutengsu; Ida Ayu Oka Martini (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Needle stick injury (NSI) remains a significant occupational health problem among healthcare workers due to continuous exposure to sharp instruments and biological hazards. This study aims to analyze the direct and indirect effects of workload and organizational culture on needle stick injury through risk perception among healthcare workers in Denpasar City, Indonesia. A quantitative associative causal design was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Data were collected from 126 healthcare professionals, including physicians, dentists, nurses, and midwives, through a structured questionnaire. The findings indicate that workload and organizational culture do not directly influence needle stick injury. However, workload has a significant positive effect on risk perception, and risk perception is positively associated with needle stick injury. Furthermore, risk perception significantly mediates the relationship between workload and needle stick injury, while it does not mediate the relationship between organizational culture and injury occurrence. These findings suggest that needle stick injury is a multicausal phenomenon shaped by the interaction of systemic pressures and psychological responses rather than isolated organizational factors. Grounded in Reason’s Swiss Cheese Model and the Cultural Theory of Risk, this study highlights the importance of integrating workload management and systemic safety interventions to strengthen occupational safety strategies in healthcare settings.